Localization of transforming growth factor-beta expression in the peri-implant tissues of dental implants coated with placental collagen - Alhijazi, Athraa Y; Khashman, Basim M; Abdul Ghani, Ban; Isaa, Eman (Journal of Baghdad College of Dentistry, 2013)
Back ground : The transforming growth factor beta (TGFB) signaling pathway is involved in many cellular processes in both the adult organism and the developing embryo including cell growth, cell differentiation, apoptosis. The interaction between implant material and surrounding tissues is believed to play a fundamental role in implant success and illustrates different expression of growth factors by different cells that involved in the formation of peri-implant tissue. The aim of this study was to localize expression of TGF B by newly formed bone tissue around surface-conditioned implants with placental collagen at different time intervals: 3 ,7,14,28, and 56 days . Materials and Methods: Commercially pure Titanium (CPTi) implants coated with collagen protein were placed in the tibia of 20 new Zealand rabbits . Immunohistochemical study for localization of TGF B in peri –implant tissue for interval periods 3 ,7,14,28, and 56 days was performed under light microscope.. Results: Positive expression of Transforming growth factor B can be detected in osteoblast, osteocyte, newly deposited matrix includes collagenous tissue and non mineralized osteoid tissue. Endothelial cells line blood vessel showed positivity too. Minerlized bone trabeculae and mature bone illustrate negative expression. Conclusion: The present study suggests that placental collagen, coated Ti implant illustrates positive expression of transforming growth factor B by osteoblast and endothelial cell that enhanced bone formation.